A high Q piezoelectric resonator as a portable VLF transmitter - Mark A. Kemp (Nature Portfolio, 2019)
Designing high radiation efficiency antennas for portable transmitters in low frequency communication systems remains a challenge. Here, the authors report on using piezoelectricity to more efficiently radiate while achieving a bandwidth eighty three times higher than the passive Bode-Fano limit.